2008
DOI: 10.1063/1.2992081
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mn-modified Pb(Mg1∕3Nb2∕3)O3–PbZrO3–PbTiO3 single crystals for high power broad bandwidth transducers

Abstract: The effect of MnO 2 addition on the dielectric and piezoelectric properties of 0.4Pb͑Mg 1/3 Nb 2/3 ͒O 3 -0.25PbZrO 3 -0.35PbTiO 3 single crystals was investigated. Analogous to acceptor doping in "hard" Pb͑Zr, Ti͒O 3 based polycrystalline materials, the Mn doped crystals exhibited enhanced mechanical Q ͑ϳ1050͒ with low dielectric loss ͑ϳ0.2% ͒, while maintaining ultrahigh electromechanical coupling k 33 Ͼ 90%, inherent in domain engineered single crystals. The effect of acceptor doping was also evident in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
90
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 17 publications
1
90
0
Order By: Relevance
“…11,12 Recently, manganese modified relaxor-PT crystals have been reported to exhibit enhanced mechanical quality factors Q m and increased field stability. 13,14 To date, however, the full matrix of electromechanical properties for rhombohedral PIN-PMN-PT:Mn single crystals has not been measured and the effect of Mn 2þ,3þ on relaxor-PT crystals is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Recently, manganese modified relaxor-PT crystals have been reported to exhibit enhanced mechanical quality factors Q m and increased field stability. 13,14 To date, however, the full matrix of electromechanical properties for rhombohedral PIN-PMN-PT:Mn single crystals has not been measured and the effect of Mn 2þ,3þ on relaxor-PT crystals is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, aging ferroelectrics to align defect dipoles could achieve improved electromechanical responses. 19,29 Our simulations suggest that poling the sample during the aging process is critical in controllably aligning the defect dipoles and applying an electric field perpendicular to the poling direction to realize optimal electro-strain coupling during device operation.The magnitude of the built-in electric field arising from dipole impurities depends on the concentration and magnitude of defect dipoles. For a collection of dipoles (q = 0.1 e) aligned along −y, the shape of the P x -E x loop evolves from square (n = 0.6%) to slim, pinched (n = 0.8%), and eventually becomes double loops (n = 1.2 %) as the concentration increases ( Figure 2a).…”
mentioning
confidence: 99%
“…Experimentally, aging ferroelectrics to align defect dipoles could achieve improved electromechanical responses. 19,29 Our simulations suggest that poling the sample during the aging process is critical in controllably aligning the defect dipoles and applying an electric field perpendicular to the poling direction to realize optimal electro-strain coupling during device operation.…”
mentioning
confidence: 99%
“…Therefore, over the past few years, tremendous efforts have been made to improve the temperature stability of the properties, two potential approaches have been adopted so far: shifting T c /T rt to higher temperature by composition tuning, and taking advantage of the engineered domain configuration in single crystals. 3 In the first method, through elements substituting and/or adding of other end-members, numerous new higher T c /T rt binary and ternary material systems were developed, including Pb(In 1/2 Nb 1/2 )-PbTiO 3 (PIN-PT), 6,7 Pb(Yb 1/2 Nb 1/2 )-PbTiO 3 (PYN-PT), 8,9 Pb(Sc 1/2 Nb 1/2 )-PbTiO 3 (PSN-PT), 10 Pb(In 1/2 Nb 1/2 )-Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 (PIN-PMN-PT), [11][12][13][14][15] Pb(Mg 1/3 Nb 2/3 )O 3 -PbZrO 3 -PbTiO 3 (PMN-PZ-PT), [16][17][18][19] and Pb(Sc 1/2 Nb 1/2 )-Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 (PSN-PMN-PT), 20 etc. However, it was found that the temperature stability remained unsolved despite of the high T c /T rt .…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20]30 The PMN-PZ-PT ternary system, which can be regarded as the combination of PMN-PT and PZT, was reported to possess high ferroelectric phase transition temperatures and high coercive fields, the as-grown PMN-PZ-PT single crystals were considered to be the second generation relaxor-PT crystals. 3 (PMN-PFN-PZ-PT) was reported with high d 33 > 600 pC/N and enhanced ferroelectric phase transition temperature.…”
mentioning
confidence: 99%